Ecodiversidad en la Reserva Ecológica Arenillas para el desarrollo ecoturístico - Cuenca Ullaguari, Katty Maricela (My University, 2020)
The present study was carried out in the Arenillas Ecological Reserve REA located between the Arenillas and Huaquillas cantons of the province of El Oro to the southwest of Ecuador near the border with Peru, whose general objective is to evaluate the relationship between culture and biodiversity of the Reserve through techniques and instruments for ecotourism development. Through the bibliographic information obtained and research carried out in situ in the study area, the relationship between culture and biodiversity was identified, being the strongest relationship, natural landscapes and archaeological sites with ecosystems; the average relation, the flora with the traditions and the low relation, the fauna with the historical architecture arts and the gastronomy. This also makes it easy to understand the behavior of man in nature. Regarding the ecotourism development for the reserve, it is considered as such to enhance the reserve as a product that involves existing ecodiversity. In addition to promoting its tourist attractions such as hiking, sighting of flora and fauna where you can perform activities such as cycling, camping, photography, walking, bird watching, observe the flowering of the guayacanes and other near and far routes of interpretation center of the reserve. In order to promote ecotourism development it is important to have marketing strategies such as web pages, tourist routes, digital marketing among others, which allow highlighting what the reserve has and weighing it a tourism potential that allows the economic, environmental and sociocultural development of the Province.
El presente estudio se realizó en la Reserva Ecológica Arenillas REA ubicada entre los cantones Arenillas y Huaquillas de la provincia de el Oro al suroccidente del Ecuador cerca de la frontera con Perú, cuyo objetivo general es evaluar la relación entre cultura y biodiversidad de la reserva mediante técnicas e instrumentos para el desarrollo ecoturístico. A través de la información bibliográfica obtenida e investigación realizada in situ en el área de estudio se identificó la relación entre cultura y biodiversidad siendo la relación más fuerte, los paisajes naturales y sitios arqueológicos con los ecosistemas; la relación media, la flora con las tradiciones y la relación baja, la fauna con las artes arquitectura históricas y la gastronomía. Esto también facilita entender el comportamiento del hombre en la naturaleza. En cuanto al desarrollo ecoturístico para la reserva se considera como tal potenciar a la reserva como un producto que involucre la ecodiversidad existente. Además de fomentar sus atractivos turísticos como el senderismo, avistamiento de flora y fauna donde se puede realizar actividades como el ciclismo, camping, fotografía, caminata, avistamiento de aves, observar el florecimiento de los guayacanes y demás recorridos cercanos y lejanos de centro de interpretación de la reserva. Para alcanzar fomentar el desarrollo ecoturístico es importante contar con estrategias de marketing como páginas web, rutas turísticas, marketing digital entre otras, que permitan destacar con lo que cuenta la reserva y ponderarla un potencial turístico que permite el desarrollo económico, ambiental y sociocultural de la provincia.
Keywords: BIODIVERSIDAD; ECODIVERSIDAD; PRODUCTO ECOTURISTICO; RESERVA ECOLOGICA ARENILLAS